Analysis of the shipping industry’s insurance claims record - Chan, Chang Qing. (2011)
This report provides insights of the Final Year Project topic on The Shipping Industry’s Claims Records. The students undertaking this project are Chan Chang Qing, Mohamad Shahril Bin Zainuddin and Wong Yun Kay, and will hereafter be referred to as 'the team'. Insurance claims have contributed to the rising costs of shipping through increasing insurance premiums and deductibles. Though the magnitude of insurance cost as part of vessel operating costs is not as significant as crewing costs, it should not be overlooked by the industry. Therefore with this background, this research studies and identifies three causes that contribute to the rising trend of the marine insurance claims, forming the basis of the literature review. The team will draw conclusions from the literature reviews on how these causes impact the marine insurance industry, and ultimately, result in increase in shipping costs.